Contactless and nondestructive evaluation of residual stress distribution in modified and pure HDPE materials using a novel terahertz method and line-scan thermographic technique; Composites Part A: Applied Science and Manufacturing; Vol. 183 - Zhu Pengfei; Hai Zhang; Santulli Carlo; Sfarra S. Stefano; Usamentiaga R. Ruben; Vavilov V. P. Vladimir Platonovich; Maldague X. Xavier (2024, 2024)
Optical-stress properties were always studied at the elastic stage and at wavelengths shorter than terahertz (THz) radiation. Until present, the relationship between plastic strain and refractive index has not been fully understood. In this work, a novel THz method and line-scan thermographic technique are used for quantitative evaluation of the residual stress in the pure HDPE, as well as in the HDPE mixed with 5% by weight of wastepaper plus 5% by weight of chopped basalt as fillers. A new theory considering both influences from the sample thickness and the refractive index difference is proposed, thus allowing to improve the measurement accuracy. For the first time, the stress-optic constant and thermal diffusivity have been applied to characterize the residual stress.. The experiments suggest that, after stretching, the initial isotropic material transits into a material with highly anisotropic optical properties in THz band. This observation is useful when describing the conventional bi-refringence phenomenon. Finally, the residual stress distribution was calculated based on the proposed techniques.